Molded body and solution comprising aromatic polyamide and / or aromatic polyamideimide, and production method therefor

JP2025042591APending Publication Date: 2025-03-27TORAY INDUSTRIES INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024148629
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-14
Filing Date
2024-08-30
Publication Date
2025-03-27

Smart Images

  • Figure 2025042591000001
    Figure 2025042591000001
  • Figure 2025042591000002
    Figure 2025042591000002
  • Figure 2025042591000003
    Figure 2025042591000003
Patent Text Reader

Abstract

To provide a molded body and a solution containing aromatic polyamide and / or aromatic polyamideimide, which allow coexistence of excellent filler dispersibility, durability, and colorless transparency.SOLUTION: A molded body comprises an aromatic polyamide and / or an aromatic polyamideimide, wherein the aromatic polyamide and / or aromatic polyamideimide contains at least one group selected from monoalkoxysilyl groups, dialkoxysilyl groups, and trialkoxysilyl groups, and / or contains a silanol group, and also comprises a siloxane bond.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a molded article, a solution, and a production method containing an aromatic polyamide and / or an aromatic polyamideimide. [Background technology]

[0002] In recent years, from the viewpoints of design freedom and light weight, the development of optical devices and sensors using transparent resins as components that have traditionally been made of inorganic glass has been actively promoted. In particular, the use of transparent resins as optical components such as optical lenses and diffraction grating elements has been studied, due to the advantage that the surface shape and physical properties can be easily processed. In addition to excellent heat resistance, chemical resistance, and shape stability, such transparent resins are required to have colorless transparency and a high refractive index to meet the requirements of optical design. These required physical properties can sometimes be satisfied by including inorganic compounds as fillers, and for example, the addition of titanium oxide (TiO2) can increase the refractive index.

[0003] For example, siloxane resin is used as a resin material with excellent optical properties, and a method of copolymerizing it with a different polymer such as polyamide or polyimide to improve processability and mechanical strength has been reported. For example, Patent Documents 1 and 2 disclose a film of a copolymer of a structural unit derived from an aromatic polyamide and a silicon-containing compound. Patent Document 3 discloses a method for producing a polyamide silicone copolymer. Patent Document 4 discloses a silyl-based inorganic surface modifier containing an aromatic polyamide. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2013-166809 A [Patent Document 2] JP 2013-166810 A [Patent Document 3] JP 2011-79946 A [Patent Document 4] WO2017 / 130905 publication Summary of the Invention [Problem to be solved by the invention]

[0005] However, the aromatic polyamide copolymer films disclosed in Patent Documents 1 and 2 have high light transmittance, heat resistance, and acetone resistance, but are copolymerized in such a way that aromatic polyamide is bonded to both ends of the molecular chain centered on a siloxane structure, and therefore tend to become high-viscosity resins, and when an inorganic filler is added, the dispersibility deteriorates, causing the filler to aggregate, or the filler may precipitate and become white during molding. The copolymer described in Patent Document 3 is copolymerized with a modified siloxane having amino groups at both ends, so that chemical resistance may decrease, and the filler may become difficult to disperse due to high viscosity. In addition, the surface modifier described in Patent Document 4 has excellent affinity with fillers, but is poor in moldability and chemical resistance.

[0006] The present invention aims to provide a molded article having excellent filler dispersibility by preparing a molded article containing an aromatic polyamide and / or aromatic polyamideimide containing an alkoxysilyl group or a silanol group, or a solution containing an aromatic polyamide and / or aromatic polyamideimide having such functional groups at its terminals, and to provide a molded article having excellent durability and colorless transparency at the same time in the molded article. [Means for solving the problem]

[0007] In order to achieve the above object, the present invention is characterized as follows. The molded article is made of an aromatic polyamide and / or an aromatic polyamideimide, and the aromatic polyamide and / or aromatic polyamideimide contains at least one of a monoalkoxysilyl group, a dialkoxysilyl group, and a trialkoxysilyl group, and / or a silanol group, and also contains a siloxane bond. Effect of the Invention

[0008] According to the present invention, a molded article having excellent filler dispersibility can be provided by the solution of the present invention, and the molded article of the present invention can simultaneously achieve moldability, durability, and colorless transparency. Therefore, the solution and molded article of the present invention can be suitably used as optical members, particularly, display materials, diffractive optical elements, optical lenses, and the like. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The molded article of the present invention is characterized by containing at least one of monoalkoxysilyl groups, dialkoxysilyl groups, and trialkoxysilyl groups, and / or silanol groups derived from these groups, and also containing siloxane bonds. By containing siloxane bonds, it is possible to improve solvent resistance by crosslinking between molecular chains and increasing the molecular weight. By containing alkoxysilyl groups and / or silanol groups, it is possible to improve affinity with fillers by hydrogen bonds and intermolecular forces, and it is possible to obtain a molded article with high transparency. Since a higher effect can be expected as the number of bonding points increases, it is preferable to contain a trialkoxysilyl group among the alkoxysilyl groups. In addition, it is more preferable that the monoalkoxysilyl group, dialkoxysilyl group, trialkoxysilyl group, and / or silanol group have any of the structures represented by the following chemical formulas (I), (II), and (III). Here, the silanol group is derived from the alkoxysilyl group, but is not limited thereto.

[0010] Chemical formula (I): [ka]

[0011] R 1 , R 2 is -H, -Ph, or an alkyl group having 4 or less carbon atoms; R 3 is either -H or an alkyl group having 4 or less carbon atoms.

[0012] Chemical formula (II): [ka]

[0013] R 4 is -H, -Ph, or an alkyl group having 4 or less carbon atoms; R 5 , R 6 is either -H or an alkyl group having 4 or less carbon atoms.

[0014] Chemical formula (III): [ka]

[0015] R 7 , R 8 , R 9 is either -H or an alkyl group having 4 or less carbon atoms.

[0016] The molded article of the present invention is characterized by containing an aromatic polyamide and / or an aromatic polyamideimide. By containing the above polymer, excellent shape stability resulting from a rigid molecular structure and hydrogen bonds, and a high refractive index resulting from the high electron density of the aromatic ring can be obtained. The aromatic polyamide and / or aromatic polyamideimide in the present invention preferably contains a structural unit represented by the following chemical formula (IV).

[0017] Chemical formula (IV): [ka]

[0018] Ar 1 , Ar 2 is any aromatic group.

[0019] The aromatic polyamide of the present invention is preferably aramid. Here, aramid is an aromatic polyamide that does not have a carboxylic acid (-COOH) group at the ortho position of the carbonyl group that forms the amide group, and examples of the structures include those of the following chemical formulas (V) to (VII). However, the structures shown in the chemical formulas (V) to (VII) are examples and do not limit the structure of the aramid in the present invention.

[0020] Chemical formula (V): [ka]

[0021] Ar 3 is any aromatic group, R 10 is -H, an aliphatic group having 1 to 5 carbon atoms, -CF3, -CCl3, -OH, -F, -Cl, -Br, -OCH3, a silyl group, or a group containing an aromatic ring.

[0022] Chemical formula (VI): [ka]

[0023] Ar 4 is any aromatic group, R 11 is -H, an aliphatic group having 1 to 5 carbon atoms, -CF3, -CCl3, -OH, -F, -Cl, -Br, -OCH3, a silyl group, or a group containing an aromatic ring.

[0024] Chemical formula (VII): [ka]

[0025] Ar 5 is any aromatic group, R 12 is -H, an aliphatic group having 1 to 5 carbon atoms, -CF3, -CCl3, -OH, -F, -Cl, -Br, -OCH3, a silyl group, or a group containing an aromatic ring.

[0026] The aromatic polyamideimide of the present invention may be, for example, a polyamideimide having both an amide group and an imide group in its structural unit as shown in chemical formula (VIII), or a polyamideimide having a diimide as shown in chemical formula (IX) copolymerized with the aromatic polyamide structure as described above. Either case is acceptable in the present invention.

[0027] Chemical formula (VIII): [ka]

[0028] Ar 6 is any aromatic group, R 13 is -H, an aliphatic group having 1 to 5 carbon atoms, -CF3, -CCl3, -OH, -F, -Cl, -Br, -OCH3, a silyl group, or a group containing an aromatic ring.

[0029] Chemical formula (IX): [ka]

[0030] Ar 7 is any aromatic group, R 14 is -H, an aliphatic group having 1 to 5 carbon atoms, -CF3, -CCl3, -OH, -F, -Cl, -Br, -OCH3, a silyl group, or a group containing an aromatic ring.

[0031] Of the above, the aromatic polyamide and / or aromatic polyamideimide constituting the solution of the present invention is preferably an aromatic polyamide, since this can increase the rigidity of the film obtained by drying the solvent.

[0032] The aromatic polyamide and / or aromatic polyamideimide constituting the solution of the present invention is represented by the formula (IV) Ar 1 and / or Ar 2 It is preferable that the copolymer contains a structural unit represented by any one of the following chemical formulas (X) to (XII).

[0033] Chemical formula (X): [ka]

[0034] R 15 is -H, an aliphatic group having 1 to 5 carbon atoms, -CF3, -CCl3, -OH, -F, -Cl, -Br, -OCH3, a silyl group, or a group containing an aromatic ring.

[0035] Chemical formula (XI): [ka]

[0036] R 16 , R 17 is -H, an aliphatic group having 1 to 5 carbon atoms, -CF3, -CCl3, -OH, -F, -Cl, -Br, -OCH3, a silyl group, or a group containing an aromatic ring.

[0037] Chemical formula (XII): [ka]

[0038] R 18 is a group containing a Si atom, a group containing a P atom, a group containing a S atom, a halogenated hydrocarbon group, a group containing an aromatic ring, or a group containing an ether bond (however, structural units having these groups may be present in the molecule).

[0039] Among the above, it is particularly preferable that the polymer contains structural units represented by the following chemical formulas (XIII) and / or (XIV) in order to achieve high rigidity.

[0040] Chemical formula (XIII): [ka]

[0041] R 19is any aromatic group, or any alicyclic group.

[0042] Chemical formula (XIV): [ka]

[0043] R 20 is any aromatic group, or any alicyclic group.

[0044] The molded article of the present invention preferably contains a filler having an OH group on its surface. Examples of fillers having an OH group on their surface include inorganic oxides and organic compositions having an alcohol group or a carboxylic acid group, but inorganic oxides are particularly preferable in terms of increasing the refractive index and hardness of the molded article. Examples of inorganic oxides include, but are not limited to, silica (SiO2), aluminum oxide (Al2O3), zinc oxide (ZnO), zirconium oxide (ZrO2), titanium oxide (TiO2), antimony oxide (Sb2O3), and indium tin oxide (In2O3). When the filler has an OH group on its surface, it interacts with the siloxane group and is less likely to aggregate in the molded article, so that the filler can exhibit its inherent properties, such as refractive index and hardness, without reducing them. In addition to the above filler, the molded article may contain organic or inorganic pigments, dyes, or antioxidants for the purpose of suppressing deterioration and coloring of the molded article. Furthermore, although there are no limitations on the particle size of the filler, in the case of optical applications, a particle size of 150 nm or less is preferred because this suppresses light scattering and allows for the production of molded articles with high transparency.

[0045] The molded article of the present invention preferably contains 10 parts by weight or more and 500 parts by weight or less of the filler having OH on the surface relative to 100 parts by weight of the polymer in the molded article. More preferably, it is 50 parts by weight or more and 500 parts by weight or less, and even more preferably, it is 100 parts by weight or more and 400 parts by weight or less. If the content of the filler is less than 10 parts by weight, the expected effect of adding the filler may not be obtained. If the content of the filler is more than 500 parts by weight, the filler may aggregate or saturate, causing deterioration of the shape and mechanical strength of the molded article and reduction in transparency.

[0046] The solution of the present invention is characterized by containing an aromatic polyamide and / or aromatic polyamideimide to which a functional group containing at least one of a monoalkoxysilyl group, a dialkoxysilyl group, and a trialkoxysilyl group is bonded as a terminal functional group. By containing the terminal functional group, the terminal functional group can interact with the filler to obtain high dispersibility. Among the above terminal functional groups, it is preferable that the terminal functional group has a structure represented by the following chemical formulas (XV) to (XVII).

[0047] Chemical formula (XV): [ka]

[0048] R 21 , R 22 is -H, -Ph, or an alkyl group having 4 or less carbon atoms; R 23 is either -H or an alkyl group having 4 or less carbon atoms.

[0049] Chemical formula (XVI): [ka]

[0050] R 24 is -H, -Ph, or an alkyl group having 4 or less carbon atoms; R 25 , R 26is either -H or an alkyl group having 4 or less carbon atoms.

[0051] Chemical formula (XVII): [ka]

[0052] R 27 , R 28 , R 29 is either -H or an alkyl group having 4 or less carbon atoms. The solution of the present invention contains an aprotic solvent. Here, the aprotic solvent is a polar solvent that does not have proton (hydrogen ion) donating properties, such as N-methyl-2-pyrrolidone (NMP), N,N-dimethylacetamide (DMAc), N,N-dimethylisobutyramide, 3-methoxy-N,N-dimethylpropanamide, tetrahydrofuran, γ-butyrolactone, ethyl acetate, acetonitrile, dimethylformamide, and dimethylsulfoxide.

[0053] The content of the aromatic polyamide and / or aromatic polyamideimide in the solution of the present invention is not limited, but from the viewpoint of moldability, it is preferably 5% by weight or more and 50% by weight or less based on the entire solution.

[0054] When it is necessary to identify the chemical structure, functional groups, and composition ratio of the aromatic polyamide, aromatic polyamideimide, filler, aprotic solvent, and other ingredients that make up the molded body and solution of the present invention, each component separated by a combination of techniques such as chromatography, distillation, separation, and reprecipitation can be analyzed by a combination of nuclear magnetic resonance (NMR), Fourier transform infrared spectroscopy (FT-IR), mass spectrometry (MS), elemental analysis, single crystal structure analysis, and the like.

[0055] The molded article of the present invention preferably has a haze of 0.0% or more and 3.0% or less. If the haze is more than 3.0%, the visibility, brightness, and light collection of transmitted light may decrease when used as an optical element due to light scattering. The haze is more preferably 0.0% or more and 2.5% or less, and even more preferably 0.0% or more and 2.0% or less. In order to keep the haze within the above range, it is effective to set the amount of filler contained in the molded article to the upper limit of the above range or less and reduce the inclusion of foreign matter.

[0056] The molded article of the present invention preferably has a light transmittance of 95% or more and 100% or less at a wavelength of 380 nm. More preferably, the light transmittance at a wavelength of 380 nm is 97% or more and 100% or less. By making the light transmittance at a wavelength of 380 nm 95% or more and 100% or less, a molded article with higher colorlessness can be obtained. For example, the yellowness index (YI), which is an index showing coloring, can be reduced to 0 or more and 3.0 or less. When the YI is within the above range, the color tone of the light source is not easily impaired when used as an optical element. In order to make the light transmittance at a wavelength of 380 nm within the above range, it is effective to make the terminal functional group of the aromatic polyamide and / or aromatic polyamideimide a functional group having an alkoxysilyl group and to add a filler having an OH group on the surface.

[0057] The molded article of the present invention preferably has an elastic modulus of 6.0 GPa or more and 12.0 GPa or less as measured by an atomic force microscope (AFM). More preferably, it is 6.5 GPa or more and 12.0 GPa or less. If the elastic modulus is less than 6.0 GPa, the molded article or film is likely to break or be damaged when used. By setting the elastic modulus of the molded article within the above range, the strength is improved and the molded article is less likely to break or deform, or is less likely to be scratched. For example, a pencil hardness of 5H or more can be obtained. The upper limit of the pencil hardness is 10H or less.

[0058] Here, the elastic modulus obtained by AFM is measured by performing force curve mapping measurement of AFM. AFM is a scanning probe microscope that obtains information about the surface of a sample by utilizing the atomic force between the sample and a probe (probe). While changing the distance between the sample and the probe attached to the cantilever, the force acting on the probe (the amount of deflection of the cantilever) is measured to obtain a force curve. This force curve contains various information about the sample surface, and various physicochemical properties of the sample surface can be evaluated by analyzing the force curve. In the force curve mapping measurement, the force curve is obtained by scanning parallel to the sample surface at multiple points on the sample surface, and the sample is fixed to the sample fixing stage of the AFM, and the shape image of the sample is measured in PeakForceQNM mode (a mode in which the force curve is continuously and automatically measured at multiple points). The elastic modulus of the sample can be evaluated by analyzing the elastic modulus using existing software or the like based on the results of the force curve mapping measurement. It is preferable that the molded body of the present invention has resistance to acetone. Here, "resistance to acetone" means that the material is evaluated in accordance with JIS K5600-6-1:1999 (method 3) and judged to be "resistant." The detailed items are specified as follows. Dimensions: 30mm x 30mm Thickness: 20μm Test liquid: Acetone Drop location: Center of sample (test plate) Washing after the test: running water Duration: 30 minutes Evaluation: If any of the following (a) to (c) is met, it is judged as "not resistant." If none of the following is met, it is judged as "resistant." (a) When placed on a horizontal table, the difference between the lowest and highest points of the test plate is 3 mm or more. (b) The test plate is wound into a roll, forming one or more revolutions. (c) The haze after the test is at least 1% greater than the haze before the test.

[0059] The film for preparing the test plate is made according to the following steps (i) to (v). (i) The resin is dissolved in N-methyl-2-pyrrolidone. (ii) The polymer solution obtained in (i) is spread on a support plate. (iii) The polymer solution spread on the support plate is dried at 120°C for 5 minutes. (iv) The film is peeled off from the glass plate and fixed to a metal frame. (v) The film is heat treated at 120°C for 20 minutes and at 300°C for 1 minute.

[0060] In order to have resistance to acetone, it is effective that the aromatic polyamide and / or aromatic polyamideimide contained in the molded product contains a siloxane bond. In addition to acetone, it is more preferable that the molded product has resistance to aprotic solvents such as NMP and DMAc and alcohols, and the durability to these solvents can be evaluated in the same manner as above.

[0061] The refractive index of the molded article of the present invention is preferably 1.70 or more and 2.10 or less. More preferably, the refractive index is 1.70 or more and 2.00 or less, and even more preferably, 1.80 or more and 2.00 or less. When the refractive index is within the above range, the total reflection angle becomes large, and the viewing angle and light collection efficiency of the optical element can be improved. When the refractive index is within the above range, it is effective to add a high refractive index filler such as TiO2 or ZrO2 in an amount within the above range to the aromatic polyamide and / or aromatic polyamideimide containing the above-mentioned alkoxysilyl group and / or silanol group. In particular, it is effective to use the solution of the present invention as a raw material to produce a molded article in order to achieve both a high refractive index, acetone resistance, and low haze.

[0062] The solution of the present invention preferably has an average hydrodynamic radius measured by dynamic light scattering of 0 nm or more and 1000 nm or less, more preferably 0 nm or more and 500 nm or less. If the hydrodynamic radius is greater than 1000 nm, the solution or molded product may lose transparency or the refractive index may decrease due to aggregation of polymers or fillers in the solution or impurities. In order to make the hydrodynamic radius within the above range, it is effective to make the terminal functional group of the aromatic polyamide and / or aromatic polyamideimide a functional group having an alkoxysilyl group and to add a filler having an OH group on the surface.

[0063] Hereinafter, the method for producing a molded article and a solution containing an aromatic polyamide and / or an aromatic polyamideimide of the present invention will be described using an aromatic polyamide as an example, but the present invention is not limited thereto.

[0064] Various known methods such as solution polymerization and precipitation polymerization can be used to obtain aromatic polyamides. For example, when polymerizing aromatic polyamides by solution polymerization, the raw materials, acid dichloride and diamine, can be polymerized by reacting them in the above-mentioned aprotic solvent at low temperature. In order to suppress the deactivation of the acid dichloride, it is preferable to set the moisture content of the solvent used in the polymerization to 500 ppm or less (based on mass, the same applies below), more preferably 200 ppm or less. Here, since an equivalent molar ratio of the acid dichloride and the diamine tends to produce a polymer with an ultra-high molecular weight, it is preferable to adjust the molar ratio so that one is 96.0 to 99.8% of the other, more preferably 96.0 to 99.0%. When polymerization is performed at this molar ratio, the diamine becomes excessive relative to the acid dichloride, and the terminal functional group becomes an amino group. In addition, the polymerization reaction of aromatic polyamides is accompanied by heat generation, and it is preferable to set the temperature of the solution during polymerization to 40°C or less. If the temperature exceeds 40°C, side reactions may occur, resulting in an insufficient degree of polymerization or coloring. It is more preferable to keep the solution temperature during polymerization at 30°C or lower.

[0065] When acid dichloride and diamine are used as raw materials, hydrogen chloride is produced as a by-product during the reaction, and the resulting aromatic polyamide solution is highly acidic. This solution is highly corrosive and may not be usable as a varnish for forming a coating film on a substrate in the device manufacturing process.

[0066] Methods for removing the by-product hydrogen chloride include a method in which a neutralizing agent is added during polymerization to neutralize and remove hydrogen chloride, and a method in which the polymer is precipitated and isolated.

[0067] When hydrogen chloride is neutralized and removed during polymerization, for example, a method of neutralizing with an inorganic neutralizing agent such as lithium carbonate, calcium carbonate, or calcium hydroxide can be mentioned. When neutralizing with an inorganic neutralizing agent, an inorganic salt (e.g., lithium chloride, etc.) generated by the neutralization reaction is contained in the solution. This inorganic salt ionizes in the solvent and coordinates with the amide group of the aromatic polyamide, thereby acting as a dissolving aid in the solvent, and is therefore effective in improving the pot life of the solution and suppressing devitrification during film formation. However, since a washing process is required to remove the inorganic salt during the film formation process, it may not be possible to use it as a varnish depending on the device manufacturing process.

[0068] In the present invention, a method of precipitating the polymer and separating it from hydrogen chloride is preferred. When precipitating and isolating the polymer, the polymer solution obtained by solution polymerization is mixed with a large amount of a poor solvent such as water to precipitate the polymer as a solid, and the polymer and hydrogen chloride can be separated by separating it from the solution by filtration or the like. The isolated polymer can be redissolved in the aprotic solvent described above to make it into a solution. By precipitating the polymer and separating it from hydrogen chloride, it does not contain neutralization products generated by the reaction of the neutralizing agent with hydrogen chloride, and the terminal functional group can be easily modified.

[0069] By adding a silylation reagent corresponding to the terminal functional group of the polymer immediately after polymerization, an alkoxysilyl group can be introduced to the terminal functional group. When an aromatic polyamide is obtained by polycondensation of an acid dichloride and a diamine, the terminal functional group immediately after polymerization is a carboxylic acid group or an amino group. As described above, when polymerization is performed under conditions in which the diamine is in excess, the terminal functional group becomes an amino group, so it is preferable to add an electrophilic reagent containing at least one of a monoalkoxysilyl group, a dialkoxysilyl group, and a trialkoxysilyl group as a side chain to the obtained polymer, and specifically, isocyanate-based, acid chloride-based, and ester-based reagents can be mentioned. The aromatic polyamide thus obtained containing at least one of a monoalkoxysilyl group, a dialkoxysilyl group, and a trialkoxysilyl group as a terminal functional group is dissolved in an aprotic solvent, and a filler having an OH group on the surface is added to obtain the solution of the present invention.

[0070] The molded article of the present invention is preferably obtained by casting the solution of the present invention onto a substrate and / or a mold and curing it. The material and shape of the substrate and / or mold onto which the solution is cast, and the casting method are not limited, and any method can be used depending on the purpose and use of the molded article. For example, when casting the solution onto a substrate, known methods such as die coating, roller coating, wire bar coating, and gravure coating can be selected. Examples of the mold shape include a diffraction grating type, a lens type, and a moth eye type. The solution is cured via siloxane condensation, and the condensation may be started at any timing by directly contacting a protic reagent such as an inorganic acid or an organic acid as a liquid and / or gas, or by adding an initiator that generates protons or cations by light and / or heat. In the present invention, from the viewpoint of the shape of the molded article and the simplicity of the method, it is particularly preferable to use a method in which a solution to which a photocation initiator has been added in advance is cast and then cured by irradiating light.

[0071] The molded article and solution containing the aromatic polyamide and / or aromatic polyamideimide of the present invention can be suitably used as optical elements such as optical lenses, diffractive optical elements, and sensor lenses, display materials, hard coat materials, and raw materials thereof. EXAMPLES

[0072] The present invention will be described in more detail below with reference to examples. The physical properties of the molded article of the present invention were evaluated in the form of a film, for example. The film to be subjected to the physical property evaluation was produced using the solution of the present invention according to the following method.

[0073] First, the sample solution was cast in the form of a film on a glass plate using an applicator. At this time, the temperatures of the sample solution, the glass plate, and the casting atmosphere were room temperature. The cast thickness was adjusted so that the film thickness after the solvent was dried was 10 μm. Next, the glass plate was placed in a hot air oven, and dried for 10 minutes at Tb-50°C, where Tb is the boiling point of the aprotic solvent constituting the solution (in the case of a mixed solvent, the boiling point of the solvent with the highest boiling point among the solvents contained in 30 mass% or more of the total solvent amount). The dried film was taken out of the oven together with the glass plate, air-cooled for 5 minutes, and then irradiated with light (710 mJ) using an ultraviolet irradiator (mercury lamp). Next, drying was performed under the condition of Tb+100°C for 1 minute.

[0074] In the present invention, the physical properties were measured and the effects were evaluated according to the following methods.

[0075] (1) Hayes A molded product formed into a film having a thickness of 10 μm was measured using the following device and conditions. Equipment: Turbidimeter NDH5000 (manufactured by Nippon Denshoku Industries Co., Ltd.) Light source: White LED5V3W (rated) Photodetector: Si photodiode with V(λ) filter Measurement luminous flux: φ14mm (incidence aperture φ25mm) Optical conditions: Compliant with JIS-K7136 (2000).

[0076] (2) Light transmittance at a wavelength of 380 nm The transmittance of the molded product formed into a film having a thickness of 10 μm was measured using the following device to determine the light transmittance at a wavelength of 380 nm. Transmittance (%)=(Tr1 / Tr0)×100

[0077] Here, Tr1 is the intensity of light that has passed through the molded body, and Tr0 is the intensity of light that has passed through the air at the same distance but does not pass through the molded body. Equipment: UV measuring instrument U-3410 (Hitachi Instruments) Wavelength range: 300~800nm Measurement speed: 120nm / min Measurement mode: Transmission.

[0078] (3) Elastic modulus The molded body, which was made into a film with a thickness of 10 μm, was measured using an AFM (DimensionIcon, manufactured by Burker Corporation) in PeakForceQNM mode, and the obtained force curve was analyzed based on the JKR contact theory using the attached analysis software, NanoScopeAnalysis V1.40, to determine the elastic modulus distribution.

[0079] Specifically, following the PeakForceQNM mode manual, the cantilever's warpage sensitivity, spring constant, and tip curvature were calibrated, and then measurements were performed under the following conditions, and the resulting DMT Modulus channel data was used as one piece of elastic modulus data. Note that although the spring constant and tip curvature vary depending on the individual cantilever, we used a cantilever that met the conditions of a spring constant of 0.3 N / m to 0.5 N / m and a tip curvature radius of 15 nm or less, within the range that does not affect the measurement, for the measurement.

[0080] The above measurements were carried out on 5 randomly selected samples, and the number average of the obtained data was regarded as the elastic modulus of the sample film.

[0081] The measurement conditions are shown below. Measurement equipment: Atomic force microscope (AFM) manufactured by Burker Corporation Measurement mode: PeakForceQNM (force curve method) Cantilever: Bruker AXS SCANASYST-AIR (Material: Si, spring constant K: 0.4N / m, tip curvature radius R: 2nm) Measurement atmosphere: 23℃ in air Measurement range: 3μm square Resolution: 512×512 Cantilever movement speed: 10μm / s Maximum pressing load: 10nN. (4) Yellowness index (YI)

[0082] The molded product was made into a film with a thickness of 10 μm, and was measured at a temperature of 23° C. and a humidity of 65% RH using a spectrophotometer SE-2000 (manufactured by Nippon Denshoku Industries Co., Ltd.) conforming to ASTM D1925 (1988). The sample dimensions were 40 mm × 50 mm, and the measurement was performed in transmission mode.

[0083] (5)Pencil hardness The molded product formed into a film having a thickness of 10 μm was placed on a glass plate and measured in accordance with JIS-K5600-5-4 (1999) at a temperature of 23° C. and a humidity of 65% RH using the following device and conditions. Equipment: Surface measuring machine HEIDON-14DR (manufactured by Shinto Scientific Co., Ltd.) Weight: 750gf Angle: 45° Traveling speed: 30mm / min Travel distance: 10mm Sample substrate: glass plate Pencils used: Hi-Uni (manufactured by Mitsubishi Pencil Co., Ltd.), from softest (lowest hardness) are: 10B, 9B, 8B, 7B, 6B, 5B, 4B, 3B, 2B, B, HB, F, H, 2H, 3H, 4H, 5H, 6H, 7H, 8H, 9H, 10H Hardness evaluation: The test was carried out five times, and if there were no scratches or dents in the third to fifth tests, it was determined that the test piece had the required hardness.

[0084] (6) Resistance to acetone (durability) The evaluation shall be based on JIS K5600-6-1:1999 (Method 3). The detailed items shall be specified as follows: Dimensions: 30mm x 30mm Thickness: 10μm Test liquid: Acetone Drop location: Center of sample (test plate) Washing after the test: running water Duration: 30 minutes Evaluation: If any of the following (a) to (c) is met, it is judged as "not resistant." If none of the following is met, it is judged as "resistant." (a) When placed on a horizontal table, the difference between the lowest and highest points of the test plate is 3 mm or more. (b) The test plate is wound into a roll, forming one or more revolutions. (c) The haze after the test is at least 1% greater than the haze before the test.

[0085] The film for preparing the test plate is made according to the following steps (i) to (v). (i) The resin is dissolved in N-methyl-2-pyrrolidone. (ii) The polymer solution obtained in (i) is spread on a support plate. (iii) The polymer solution spread on the support plate is dried at 120°C for 5 minutes. (iv) The film is peeled off from the glass plate and fixed to a metal frame. (v) The film is heat treated at 120°C for 20 minutes and at 300°C for 1 minute. In Table 1, "resistant" is indicated with an ◯, and "not resistant" is indicated with an ×. Resistance to other solvents can also be evaluated in a similar manner.

[0086] (7) Refractive index The refractive index of a resin molded article having a thickness of 2.0 μm formed on a glass substrate was measured by spectroscopic ellipsometry using the following device and conditions. Equipment: High-speed spectroscopic ellipsometer (JA Woollam) Measurement wavelength: 633nm Incident angle: 50, 60.70 degrees Analysis software: WVASE32 Beam diameter: approximately 2mm x 8mm.

[0087] (8) Average hydrodynamic radius (average particle diameter) For each sample solution, the cumulant average particle size was measured by dynamic light scattering using the following device and conditions, and the obtained hydrodynamic radius r (nm) was taken as the average particle size. Equipment: ELSZ-1000 (Otsuka Electronics Co., Ltd.) Measurement conditions: Compliant with JIS-Z8826 (2005).

[0088] Example 1 In dehydrated DMAc (boiling point 165°C), 2,2'-ditrifluoromethyl-4,4'-diaminobiphenyl (TFMB) was dissolved under nitrogen flow, and the liquid temperature was cooled to 5°C in an ice water bath. While the system was kept in an ice water bath under nitrogen flow, 2-chloroterephthaloyl chloride (CTPC) was added over 30 minutes, which was 99 mol% of the total amount of diamines. After the entire amount was added, the mixture was stirred for about 1 hour to polymerize aromatic polyamide. The obtained polymerization solution was added to a large amount of pure water while stirring to solidify the polymer into a fibrous form, which was then crushed in a mixer for 5 minutes and dried in a hot air oven at 80°C for 1 hour and in a vacuum oven at 120°C for 12 hours to obtain a powder of the polymer.

[0089] The polymer was dissolved in DMAc so that the polymer concentration was 10% by mass. To silylate the terminal amino groups, 2.5 equivalents of 3-(trimethoxysilyl)propyl isocyanate was added relative to the amount of substance calculated from the number average molecular weight of the polymer, and the mixture was stirred at 60° C. for 3 hours to obtain a solution containing an aromatic polyamide (polymer A) having a trimethoxysilyl (TMS) group as a terminal functional group.

[0090] To the obtained solution of polymer A, 1 part by weight of bis(4-tert-butylphenyl)iodonium hexafluorophosphate was added as a photocation initiator and 200 parts by weight of TiO2 (particle size 20 nm) was added as a filler to 100 parts by weight of polymer A under light shielding, and the mixture was stirred for 5 minutes in a hybrid mixer. The obtained solution was cast into a film on a glass plate using an applicator at room temperature, dried at 115°C for 10 minutes in a hot air oven, and then removed from the oven and air-cooled for 5 minutes. After that, the mixture was irradiated with light (mercury lamp, 710 mJ) and dried again at 265°C for 1 minute in a hot air oven to obtain a film-like molded product made of polymer A with a thickness of 10 μm. Here, a safety oven SPH100 ​​(manufactured by Espec Corporation) was used as the hot air oven, and it was used 1 hour after the temperature display reached the set temperature with the opening and closing damper at 50%. The physical properties of the obtained molded product are shown in Table 1. The YI was 1.3 and the pencil hardness was 6H.

[0091] Example 2 A solution containing polymer B having a triethoxysilyl (TES) group as a terminal functional group and a molded product were obtained in the same manner as in Example 1, except that 3-(triethoxysilyl)propyl isocyanate was added instead of 3-(trimethoxysilyl)propyl isocyanate. The physical properties of the obtained molded product are shown in Table 1.

[0092] Example 3 A solution containing polymer C having a dimethoxysilyl (DMS) group as a terminal functional group and a molded product were obtained in the same manner as in Example 1, except that 3-(methyldimethoxysilyl)propyl isocyanate was added instead of 3-(trimethoxysilyl)propyl isocyanate. The physical properties of the obtained molded product are shown in Table 1.

[0093] Example 4 A solution containing polymer D having a monomethoxysilyl (MMS) group as a terminal functional group and a molded product were obtained in the same manner as in Example 1, except that 3-(methoxydimethylsilyl)propyl isocyanate was added instead of 3-(trimethoxysilyl)propyl isocyanate. The physical properties of the obtained molded product are shown in Table 1.

[0094] Example 5 A solution containing polymer A and a molded body were obtained in the same manner as in Example 1, except that the amount of TiO2 added was 400 parts by weight per 100 parts by weight of polymer A. The physical properties of the obtained molded body are shown in Table 1. The YI was 3.1 and the pencil hardness was 5H.

[0095] Example 6 A solution containing polymer A and a molded body were obtained in the same manner as in Example 1, except that the amount of TiO2 added was 50 parts by weight per 100 parts by weight of polymer A. The physical properties of the obtained molded body are shown in Table 1.

[0096] Example 7 A solution containing polymer A and a molded body were obtained in the same manner as in Example 1, except that the amount of TiO2 added was 500 parts by weight per 100 parts by weight of polymer A. The physical properties of the obtained molded body are shown in Table 1.

[0097] Example 8 A solution containing polymer A and a molded body were obtained in the same manner as in Example 1, except that 10 parts by weight of TiO2 was added relative to 100 parts by weight of polymer A. The physical properties of the obtained molded body are shown in Table 1.

[0098] Example 9 A solution containing polymer A and a molded body were obtained in the same manner as in Example 1, except that TiO2 was not added. The physical properties of the obtained molded body are shown in Table 1. The YI was 0.6 and the pencil hardness was 6H.

[0099] Example 10 A solution containing polymer A and a molded body were obtained in the same manner as in Example 1, except that the amount of TiO2 added was 600 parts by weight per 100 parts by weight of polymer A. The physical properties of the obtained molded body are shown in Table 1.

[0100] Example 11 A solution containing polymer A and a molded body were obtained in the same manner as in Example 1, except that ZrO2 was added instead of TiO2. The physical properties of the obtained molded body are shown in Table 1.

[0101] Example 12 A solution containing polymer A and a molded body were obtained in the same manner as in Example 1, except that Al2O3 was added instead of TiO2. The physical properties of the obtained molded body are shown in Table 1.

[0102] Example 13 In dehydrated DMAc (boiling point 165°C), 3,3'-diaminodiphenylsulfone (33DDS) was dissolved under nitrogen flow, and the liquid temperature was cooled to 5°C in an ice water bath. CTPC was added over 30 minutes, which was equivalent to 99 mol% of the total amount of diamines, while the system was kept in an ice water bath under nitrogen flow. After the entire amount was added, the mixture was stirred for about 1 hour to polymerize aromatic polyamide. The obtained polymerization solution was added to a large amount of pure water while stirring, so that the polymer was solidified into a fibrous form, which was then crushed in a mixer for 5 minutes, and dried in a hot air oven at 80°C for 1 hour and in a vacuum oven at 120°C for 12 hours to obtain a powder of the polymer.

[0103] The polymer was dissolved in DMAc so that the polymer concentration was 10% by mass. To silylate the terminal amino groups, 2.5 equivalents of 3-(trimethoxysilyl)propyl isocyanate were added relative to the amount of substance calculated from the number average molecular weight of the polymer, and the mixture was stirred at 60° C. for 3 hours to obtain a solution containing an aromatic polyamide (polymer E) having a trimethoxysilyl (TMS) group as a terminal functional group.

[0104] Thereafter, a solution containing polymer E and a molded article were obtained in the same manner as in Example 1. The physical properties of the obtained molded article are shown in Table 1.

[0105] Example 14 TFMB, which is equivalent to 100 mol% of the total amount of diamines, was dissolved in dehydrated DMAc at room temperature under a nitrogen stream. 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, which is equivalent to 25 mol% of the total amount of diamines, was added thereto over 15 minutes, and after the entire amount was added, the mixture was stirred for 30 minutes. Next, CTPC, which is equivalent to 74 mol% of the total amount of diamines, was added over 30 minutes. After the entire amount was added, the mixture was stirred for about 2 hours to polymerize aromatic polyamic acid. The obtained polymerization solution was added to a large amount of pure water while stirring to solidify the polymer into a fibrous form, which was then crushed in a mixer for 5 minutes and dried in a hot air oven at 80°C for 1 hour, in a vacuum oven at 100°C for 5 hours, and at 200°C for 1 hour to obtain an aromatic polyamideimide powder.

[0106] The polymer was dissolved in NMP so that the polymer concentration was 10% by mass. In order to silylate the terminal amino groups, 2.5 equivalents of 3-(trimethoxysilyl)propyl isocyanate was added relative to the amount of substance calculated from the number average molecular weight of the polymer, and the mixture was stirred at 60° C. for 3 hours to obtain a solution containing an aromatic polyamideimide (polymer F) having a trimethoxysilyl (TMS) group as a terminal functional group.

[0107] Thereafter, a solution containing polymer F and a molded product were obtained in the same manner as in Example 1. The physical properties of the obtained molded product are shown in Table 1. The YI was 3.1 and the pencil hardness was 4H.

[0108] Comparative Example 1 An aromatic polyamide (polymer G) solution not containing an alkoxysilyl group and a molded product were obtained in the same manner as in Example 1, except that 3-(trimethoxysilyl)propyl isocyanate was not added. The physical properties of the obtained molded product are shown in Table 1. The YI was 4.2 and the pencil hardness was 5H.

[0109] Comparative Example 2 A solution containing polymer G and a molded body were obtained in the same manner as in Comparative Example 1, except that TiO2 was not added. The physical properties of the obtained molded body are shown in Table 1.

[0110] Comparative Example 3 In dehydrated NMP (boiling point 202°C), TFMB, which corresponds to 100 mol% of the total diamine amount, 35 parts by weight of polysiloxane ("PSQ SR-21" manufactured by Konishi Chemical Industry Co., Ltd.) and 35 parts by weight of anhydrous lithium chloride were dissolved under a nitrogen flow until it became uniform with the naked eye, and the liquid temperature was cooled to 5°C in an ice water bath. CTPC, which corresponds to 99 mol% of the total diamine amount, was added thereto over 30 minutes while keeping the system in an ice water bath under a nitrogen flow, and after the entire amount was added, the mixture was stirred for about 1 hour to polymerize a copolymer (polymer H) having aromatic polyamides at both ends of the siloxane. The obtained polymerization solution was added to a large amount of pure water while stirring to solidify the polymer into a fibrous form, which was then crushed in a mixer for 5 minutes, dried in a hot air oven at 80°C for 1 hour and in a vacuum oven at 120°C for 12 hours to obtain a powder of polymer H.

[0111] The obtained polymer H was dissolved in NMP so that the polymer concentration was 10% by mass. To this solution, 200 parts by weight of TiO2 (particle size 20 nm) was added to 100 parts by weight of polymer A, and the mixture was stirred for 10 minutes with a hybrid mixer. The obtained solution was cast into a film on a glass plate using an applicator at room temperature, dried in a hot air oven at 115°C for 10 minutes, and then removed from the oven and air-cooled for 5 minutes. After that, the mixture was irradiated with light (mercury lamp, 710 mJ) and dried again in a hot air oven at 265°C for 1 minute to obtain a film-like molded product made of polymer H with a thickness of 10 μm. Here, the hot air oven used was a safety oven SPH100 ​​(manufactured by Espec Corporation), and was used 1 hour after the temperature display reached the set temperature with the opening and closing damper at 50%. The physical properties of the obtained molded product are shown in Table 1.

[0112] [Table 1]

Claims

1. A molded article made of an aromatic polyamide and / or an aromatic polyamideimide, the aromatic polyamide and / or the aromatic polyamideimide containing at least one of a monoalkoxysilyl group, a dialkoxysilyl group and a trialkoxysilyl group, and / or a silanol group, and containing a siloxane bond.

2. 2. The molded article according to claim 1, further comprising 10 parts by weight or more and 500 parts by weight or less of a filler having an OH group on its surface, based on 100 parts by weight of the polymer contained in the molded article.

3. A solution containing an aromatic polyamide and / or aromatic polyamideimide having a functional group containing at least one of a monoalkoxysilyl group, a dialkoxysilyl group, and a trialkoxysilyl group bonded as a terminal functional group, a filler having OH groups on its surface, and an aprotic solvent.

4. The solution according to claim 3, wherein the terminal functional group has a structure represented by at least one of the following chemical formulas (I) to (III): Chemical formula (I): 【Chemistry 1】 R 1 , R 2 is -H, -Ph, or an alkyl group having 4 or less carbon atoms; R 3 is either --H or an alkyl group having 4 or less carbon atoms. Chemical formula (II): 【Chemistry 2】 R 4 is -H, -Ph, or an alkyl group having 4 or less carbon atoms; R 5 , R 6 is either --H or an alkyl group having 4 or less carbon atoms. Chemical formula (III): 【Chemistry 3】 R 7 , R 8 , R 9 is either --H or an alkyl group having 4 or less carbon atoms.

5. 2. The molded article according to claim 1, wherein the aromatic polyamide or aromatic polyamideimide has a structural unit represented by the following chemical formula (IV): Chemical formula (IV): 【Chemistry 4】 Ar 1 , Ar 2 is any aromatic group.

6. The molded article according to claim 1, having a haze of 0.0% or more and 3.0% or less.

7. The molded article according to claim 1, having a light transmittance at a wavelength of 380 nm of 95% or more and 100% or less.

8. The molded article according to claim 1, having an elastic modulus measured by AFM of 6.0 GPa or more and 12.0 GPa or less.

9. 2. The molded body according to claim 1, which is resistant to acetone.

10. The molded article according to claim 2, having a refractive index of 1.70 or more and 2.10 or less.

11. The solution according to claim 3, which contains an inorganic oxide as a filler, and when 200 parts by weight of the inorganic oxide having an average particle size of 20 nm is contained per 100 parts by weight of aromatic polyamide and / or aromatic polyamideimide, the hydrodynamic radius measured by dynamic light scattering is 1000 nm or less.

12. An optical element comprising the molded article according to claim 8 .

13. A method for producing a molded article containing an aromatic polyamide and / or an aromatic polyamideimide, comprising the steps of: casting the solution according to claim 3 onto a substrate and / or a mold; and curing the solution.

Citation Information

Patent Citations

  • Manufacturing method for polyamide silicone copolymer

    JP2011079946A

  • Aromatic polyamide film and method of manufacturing the same

    JP2013166809A

  • Aromatic polyamide film and method of manufacturing the same

    JP2013166810A

  • Aromatic polyamide surface modifier of silica sol

    WO2017130905A1